(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
The paper focuses on the perception of corruption during the COVID-19 pandemic. The research analyzes the trends of anti-corruption mobilization, also in relation to disaffection with political and associative participation. The article is a pioneering attempt to contribute to the debate on the politicization of corruption and anti-corruption strategies.